CADEIAS PRODUTIVAS DA SOCIOBIODIVERSIDADE: INCLUSÃO PRODUTIVA EM TERENOS, MS - Haideline Mertens Kuff (2023)
The production chains of native species associated with the agroforestry system have been valued as a productive strategy for sustainable land use, capable of generating socioeconomic benefits by developing local food products with socio-biodiversity inclusion. The National Plan for the Promotion of Socio-biodiversity Production Chains highlights the expansion of dietary habits with regional products and institutional purchasing policies to support trade, such as the Brazilian Food Acquisition Program (PAA) and the Brazilian National School Nourishment Program (PNAE), with the inclusion of the sustainability and agroecology perspectives in food and nutrition policies. In view of this, the aim of this study is to identify new production chains based on the use of socio-biodiversity food plants, taking into account productive inclusion. The study was quantitative with exploratory and descriptive character and data collection consisted of questionnaires applied in person with family farmers in the municipality of Terenos - MS, with the approval of the Ethics Committee for Research in Human Beings of the Federal University of Mato Grosso do Sul (UFMS). 121 family farmers from 05 rural settlements located in the municipality of Terenos were interviewed and 31% participate in some association or cooperative. The survey of food plants originated from the socio-biodiversity present in the region emphasized the knowledge of the following native fruits in descending order: bocaiúva, cumbaru, jatobá, pequi and guavira. The possibilities of economic use of these, as well as the species with potential for insertion in production systems, were presented during training in the areas of handling and manipulation, enabling the legalization of products through a regulatory standard that meets the RDC ANVISA nº 49/2013, preserving the uniqueness of these foods processed in a traditional and/or artisanal way by family farming. In the formal market, as in the elaboration of the school meal menu, respecting the seasonality and diversity of the region, the production potential is observed, aiming at promoting income generation, employment, and social inclusion of family farmers, as well as the sustainability, healthier eating practices and respect for local cultural and food identity. Descriptors: Sustainable Agriculture. Family agroindustry. Biodiversity. Sustainable development. Health Surveillance.